1998
DOI: 10.1074/jbc.273.9.4838
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor Spi-1/PU.1 Interacts with the Potential Splicing Factor TLS

Abstract: Spi-1/PU.1 is an Ets protein deregulated by insertional mutagenesis during the murine Friend erythroleukemia. The overexpression of the normal protein in a proerythroblastic cell prevents its terminal differentiation. In normal hematopoiesis Spi-1/PU.1 is a transcription factor that plays a key role in normal myeloid and B lymphoid differentiation. Moreover, Spi-1/PU.1 binds RNA and interferes in vitro with the splicing process. Here we report that Spi-1 interacts in vivo with TLS (translocated in liposarcoma)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
136
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(141 citation statements)
references
References 19 publications
3
136
0
2
Order By: Relevance
“…Spi-1/PU.1 is an Ets protein that binds DNA (Klemsz et al, 1990) and RNA (Hallier et al, 1998). Spi-1/PU.1 plays an essential role in normal lymphopoiesis and myelopoiesis.…”
Section: Introductionmentioning
confidence: 99%
“…Spi-1/PU.1 is an Ets protein that binds DNA (Klemsz et al, 1990) and RNA (Hallier et al, 1998). Spi-1/PU.1 plays an essential role in normal lymphopoiesis and myelopoiesis.…”
Section: Introductionmentioning
confidence: 99%
“…NonO has signi®cant homology with PSF over a 320aa region, encompassing the RNA binding domains (Dong et al, 1993). This striking degree of homology suggested that NonO was also a splicing factor and indeed it has been shown that its depletion from nuclear extract inhibits b-globin splicing in vitro (Hallier et al, 1998). NonO may have a role in transcriptional activation (Basu et al, 1997) and was also shown to bind PU.1 an ETS family protein that can alter the splicing activity of NonO in vitro (Hallier et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…26). All other antibodies in this study were from Santa Cruz Biotechnology, Inc., and include mouse monoclonal anti-Cdk1 (clone 17, 1: 200 dilution), anti-Cdk2 (D-12, 1:200 dilution), and anti -h-actin (AC15, 1:1,000 dilution).…”
Section: Antibodies and Western Blottingmentioning
confidence: 99%